2022
DOI: 10.1101/2022.09.14.507982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional comparison of full-length palladin to isolated actin binding domain

Abstract: Palladin is an actin binding protein that is specifically upregulated in metastatic cancer cells but also co-localizes with actin stress fibers in normal cells and is critical for embryonic development as well as wound healing. Of nine isoforms present in humans, only the 90 kDa isoform of palladin, comprising three immunoglobulin (Ig) domains and one proline-rich region, is ubiquitously expressed. Previous work has also established that the Ig3 domain of palladin is the minimal binding site for F-actin. In th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that PALLD binds to actin via the Ig3 domain and is localized in various actin-rich subcellular structures, including stress fibers, focal adhesions and Z disks. 15,39 Recent studies have reported novel roles of PALLD in cell adhesion and motility, contributing to the invasive motility of cancer cells. [40][41][42] Our former research also suggested that PALLD was involved in platelet activation and arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PALLD binds to actin via the Ig3 domain and is localized in various actin-rich subcellular structures, including stress fibers, focal adhesions and Z disks. 15,39 Recent studies have reported novel roles of PALLD in cell adhesion and motility, contributing to the invasive motility of cancer cells. [40][41][42] Our former research also suggested that PALLD was involved in platelet activation and arterial thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Notably, due to its role in cell assembly and maintenance, Palladin regulates actin cytoskeleton organization and adhesion formation, 13 and in turn, contributes to the invasive and migratory nature of cancer metastatic cells. 14 , 15 , 16 Given the central role of CSCs in tumor metastasis, 17 we assumed that Palladin might be in part responsible for the metastatic and tumorigenic properties of CSCs. Although the contribution of Palladin to the invasion of various cancers, such as breast, and pancreas cancer, has been demonstrated, 16 its function and mechanism have thus far not been investigated in lung cancer, especially in LCSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Palladin is a member of the actin‐associated proteins family and is highly expressed in multiple tumor cells, including stomach, colon, breast, and pancreas cancers 11,12 . Notably, due to its role in cell assembly and maintenance, Palladin regulates actin cytoskeleton organization and adhesion formation, 13 and in turn, contributes to the invasive and migratory nature of cancer metastatic cells 14–16 . Given the central role of CSCs in tumor metastasis, 17 we assumed that Palladin might be in part responsible for the metastatic and tumorigenic properties of CSCs.…”
Section: Introductionmentioning
confidence: 99%